Therapeutic Painting and Sexual Violence Expressed by Students in Selected Secondary Schools in Bundibugyo District in Uganda - Mwijuka, Julius; Yiga, Andrew Peters; Rebecca, Joyce Bukirwa (East African Journal of Arts and Social Sciences, 2024)
Sexual violence has often caused distress to many people, and a lot has been written proposing solutions to this vice. Restoring hope among people who have been affected by sexual violence in Secondary schools in Bundibugyo District requires concerted effort and adopting ways that help to relieve the affected people of stress resulting from their experience with sexual violence. The current study focused on how therapeutic painting can be utilised to describe in detail lived experiences relating to ever-increasing sexual violence in secondary schools in the Bundibugyo district. Despite the various forms of violence that affect secondary school students, sexual violence seems to be a vice that greatly affects school children, and young children are always shy to verbally express how they are affected. Therefore, this study aimed to investigate the relationship between Visual art therapy and sexual violence expression by students in selected Secondary Schools in Bundibugyo District. The following objective guided the study: To examine the statistical relationship between therapeutic painting and sexual violence expression by students in selected Secondary Schools in Bundibugyo District. 400 S2 students participated in this study, these included; Semuriki High School-Izahura-163, Bukonjo Seed School-17, Bundikahungu Seed school-75, St Mary’s Simbya Secondary School-145. Methodology entailed methods such as in-session semi-structured interviews, observation methods, and focus group discussion. An explanatory sequential design was adopted in this study. The study established that there was a statistically significant difference in means; thus, there was a relationship between therapeutic painting and sexual violence expressed by students in selected Secondary Schools in Bundibugyo District (z =-6.736, p <0.0001). Hence, the null hypothesis was rejected. The findings led to the conclusion that therapeutic painting intervention helped to improve the expression of sexual violence among victims, helped them to gain relaxation, lost hope, and lessened the anxiety that had resulted from their experience with sexual violence